The Influence of Motivation’s Component for The Self Esteem Aspect on Nursing Student In Faculty of Nursing Jember University - Fitrio Deviantony; Dini Kurniawati; Emi Wuri Wuryaningsih (Nursing and Health Sciences Journal (NHSJ), 2021)
The success of academic achievement has a lot of determinants. Social environment background, personal characteristic, and quality of education are only a few of those factors (Zimmerman and Schunk, 1989). Own characteristics have a lot of impact on academic success, such as self-esteem, motivation, and also the will for an individual to reach their success. The purpose of this study was to analyze the influence of motivation’s component with self-esteem aspect among nursing student in the faculty of nursing Jember University.This study employed a cross-sectional study. It involved 84 respondent using purposive sampling technique from a nursing student in the faculty of the nursing University of Jember from September to November 2018. A self-administered questionnaire was designed to collect the data, including sociodemographic data, self-esteem scale, and Student motivation Scale. The data were analyzed using Spearman rank. The results showed that the median of the motivation was 50, with a minimum value of 28 and a maximum value of 140, whereas the mean value of self-esteem was 2.46 with a standard deviation of 0.56. There was a significant correlation between motivation and self-esteem (p-value: 0.001; r: 0.358). The correlation was weak and positive, which means the higher the value of motivation, the higher the self-esteem. The correlation analysis revealed that motivation has a significant effect on self-esteem. Its is show that raising motivation must be high on the list for an educational program.